The study on private employee’s perception towards leadership style of male and female leaders in Syarikat Air Melaka Berhad (SAMB) / Norulaini Zamri and Zuliyanna Zulkifli - Zamri, Norulaini; Zulkifli, Zuliyanna (Faculty of Administrative Science and Policy Studies, 2012)
This study examines the private employees’ perception towards leadership styles between male and female leaders in Syarikat Air Melaka Berhad (SAMB). In addition, the study also attempts to determine the differences in the leadership styles based on the demographic of leaders variables (age). The study also hypothesized that there are significant differences in the perceptions of the SAMB employees toward leadership styles between male and female leaders at different age, length of service and qualification of employees. Questionnaire has been used as a research instruments were used to obtain data. A total of 100 respondents were distributed all over 10 departments within SAMB as the sample of study and data was analyzed by “Statistical Package for Social Science” (SPSS Window) Version 19.0. The tests involved are cross tabulation, independent group t-test and ANOVA. The result of leadership styles between male and female leaders generally did not support the hypothesis. The democratic style of leadership demonstrates the strongest leadership style that has been practiced among the leaders in SAMB. Furthermore, the result shows neither male nor female leaders don’t have any significant difference with leadership styles. These findings show that the related factors don’t have any significant difference with leadership styles between male and female leaders in SAMB. Some suggestions have been recommended for the leaders in private sector organizations to be more favourable by their employees.